SOSIALISASI GERAKAN ANTI BULLYING DI SMA NEGERI 1 MAJENE - Tamrin, Sopian; Sulmiah, Sulmiah; Rusdi, Rusdi; Najamuddin, Najamuddin; Amandaria, Riri (Universitas Negeri Makassar, 2024)
Violence has become a concerning fact in the world of education. Education as a social arena that is expected to be an example of a non-violent environment actually shows the opposite indication. Based on the results of the observation, SMA Negeri 1 Majene was determined as the target of the socialization. This is also related to the agreement of the university-level community service team to focus activities in Majene Regency. The activity took place on May 11, 2024 in a classroom of a partner school. This activity targeted teachers. The participants who attended were teachers from various subject backgrounds. This variation is an added value of the forum in interpreting bullying from various perspectives. In general, teachers understand the meaning of bullying. However, they are less aware of how bullying practices operate in the school arena to the interpersonal level. The daily lives of students and teachers such as joking or teasing are still seen as normal habits that have no adverse effects on someone who is bullied. In fact, the practice of bullying causes psychological problems, which can interfere with the development of those who are bullied, especially among students. After this activity, it is hoped that teachers will become creative agents who spread inclusive values in the school environment. In addition, the community service team also hopes that with this activity, bullying practices will not occur in the school environment, especially in partner schools.